Race, poverty, and the traffic ticket cycle Exploring the situational context of the application of police discretion - Kent, Stephanie L. (2014)
Purpose – Through systematic observation of police decision-making behavior, the aim of this paper is to investigate what factors differentiate between citizens who receive a warning vs a ticket from police and whether the influence of those factors varies by race. The paper also explores the context of those decisions for both blacks and whites to further the understanding of the underlying mechanisms of any observed differences in the likelihood of receiving a ticket vs a warning. Design/methodology/approach – Data were collected during police ridealongs conducted in a sample of cities within Cuyahoga County, Ohio. A total of 140 ridealongs were completed, yielding a total of 312 vehicle or citizen stops. Findings – The paper finds that black citizens are more likely to receive a ticket than white citizens. However, the paper also finds important differences in the situational context of traffic stops for blacks and whites and uncover evidence of a cycle of traffic tickets and license suspensions among some black drivers. Research limitations/implications – The study demonstrates the importance of examining the underlying situational context in analyses of decision making in traffic stops. The main limitation of the analyses is that the data were limited to one county in the state of Ohio. Practical implications – The data suggests that one of the causes of the racial disparities in tickets vs warnings involves a cycle of tickets and license suspensions that occurs among some black drivers. These drivers appear to become caught up in a cycle where a compilation of prior tickets from traffic infractions, driving without insurance, or defaulting on child support payments leads to high numbers of points and subsequent license suspensions. The paper discusses some practical implications for addressing this pattern, including specific programs that could be adopted by municipalities that seek to break the cycle of repeated violation of driver’s license laws. Originality/value – Beyond identifying the impact of citizen race on the likelihood of receiving a warning vs a ticket during a traffic stop, this study contributes to the existing literature by exploring the situational context of these decisions, and identifying the ways in which variations in situational contexts help explain racial differences in outcomes in traffic stops. The identification of a traffic ticket cycle among some black drivers appears to be an original finding